FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA MENGIKUTI PENDIDIKAN PROFESI AKUNTAN - Ida Siti Mudrikah, Rispantyo & Djoko Kristianto (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2019)
The purpose of research to examine the influence of Profession Perception, Career Motivation, Economic Motivation, Quality Motivation and Cost of Education on Student Interest Participate in Accounting Profession Education partially. This research use survey method, student population of Faculty of Economics of Private University at Solo accredited B. Sampling technique using judgment sampling and Sampling Quota, got sample of student of Economic Faculty of Slamet Riyadi University (UNISRI) and Setia Budi University (USB) and Tunas Pembangunan University (UTP), so that the sample as many as 95 students, because UTP can not be done research so that only students UNISRI and USB who become the research sample. The analysis technique used multiple linear regression analysis, t test, F test, and Coefficient of Determination. The results of the research are Perception Profession, Career Motivation, Economic Motivation, Motivation of Quality have significant influence to the Interest of Following PPAk Universitas Slamet Riyadi (UNISRI) and Setia Budi University (USB) and Education Cost has no significant effect on the Interest of Following PPAk Universitas Slamet Riyadi (UNISRI) and Setia Budi University (USB).Keywords: Professional Perception, Career Motivation, Economic Motivation, Quality Motivation, Education Cost, Interest Following PPAk.